Pengaruh Digital Marketing dan Inovasi Produk Terhadap Kinerja Pemasaran pada UMKM di Kabupaten Buleleng - Kadek Dwi Lestari; I Nyoman Sujana (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2025)
innovation on the marketing performance of MSMEs in Buleleng Regency, both partially and simultaneously. This research employs a quantitative approach with a causal research design. The population consists of all MSMEs in Buleleng Regency, totalling 204 units based on data from the Department of Trade, Industry, Cooperatives, and MSMEs of Buleleng Regency. The sample comprises 47 MSMEs selected using purposive sampling. The type of data used is quantitative, sourced from both primary and secondary data. Data collection methods include questionnaires, and documentation. The analytical technique used is multiple linear regression, with hypothesis testing carried out using the t-test for partial effects and the F-test for simultaneous effects. The results show that: 1) digital marketing has an influence on marketing performance among MSMEs in Buleleng Regency; 2) product innovation affects the marketing performance of MSMEs in Buleleng Regency; and 3) digital marketing and product innovation jointly influence marketing performance.